INTELLIGENT DECISION-MAKING SYSTEMS FOR SUPPORT FOR OPERATION, MAINTENANCE PROCESSES AND REPAIR OF ON-BOARD AIRCRAFT EQUIPMENT TECHNIQUES - Azarskov , V. M.; Sitnik , O. G. (Problems of Informatization and Control, 2021)
The methods and methodology used in aircraft operation, maintenance and repair systems to solve existing problems may vary depending on the factors inherent in a particular study. But the approach characteristic of the system analysis and synthesis of the systems differing in systematic research of all classes of problems, both simple, and difficult is offered. The use of certain procedures of system analysis and synthesis of systems is aimed at obtaining the maximum amount of information needed to select the best option for the study of the goal.